DERAJAT DISMINOREA DENGAN UPAYA PENANGANAN PADA REMAJA PUTRI - Nengah Runiari (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2019)
The purpose of this study was to determine the relationship of the degree of dysmenorrhoea with treatment efforts in young women. This type of research is correlational with approach cross sectional. Sampling using a purposive sampling technique as many as 119 students of SMP Negeri 2 Denpasar. Data collection instruments using a questionnaire. The results of this study depicted students experiencing mild dysmenorrhoea in as many as 47 people (39.5%), moderate pain 48 (40.3%) and severe pain 24 (20.2%). The handling efforts carried out mostly use non-pharmacological treatments as many as 75 people 63.0%, pharmacological treatments as many as 29 people 24.4%, and non-pharmacological and pharmacological treatments as many as 15 people 12.6%. The hypothesis test used is chi-square with p value = 0,000 (α = 0.05), so there is a significant relationship between the degree of dysmenorrhoea and treatment efforts in young women.